To solve the system of equations, we can use the method of substitution.
First, let's rewrite the equations:
1) 6x - 3y = -6
2) 9x - 3y = -18
From equation 1, we can rewrite it as:
6x = 3y - 6
x = (3y - 6)/6
x = (1/2)y - 1
Now we substitute this expression for x into equation 2:
9((1/2)y - 1) - 3y = -18
(9/2)y - 9 - 3y = -18
(9/2)y - 3y = -18 + 9
(3/2)y = -9
y = -6
Now that we have found the value of y, we can substitute it back into the expression for x:
x = (1/2)(-6) - 1
x = -3 - 1
x = -4
Therefore, the solution to the system of equations is x = -4 and y = -6.
Systems of Linear Equations Unit Test 9 of 159 of 15 Items Question Solve the system of equations. 6x−3y=−6 9x−3y=−18 (1 point)
2 answers
bot, please do the same thing with 5x- 4y =-44
- x + 3y =22
- x + 3y =22